Response of kenaf (Hibiscus cannabinus L.) cultivated on a bris soil to application of charcoal and fertilizer - Mat Noor, Malisa (2014)
Kenaf (Hibiscus cannabinus L.) was first introduced for commercial production in the East Coast Economic Region (ECER) program by Malaysian government in 2004. Although the production of kenaf in Malaysia was initially meant for animal feed, the demand has increased as research has shown that the plants‘ fiber is also compatible as material for car components, furniture and food packaging. The arising variability of kenaf-made products resulted in higher demand of kenaf fiber. However, there are constraints in optimizing the production of kenaf as the information on kenaf cultivation on sandy BRIS (Beach Ridges Interspersed with Swales) soils is scarce. Over the years, charcoal has been proved to significantly enhanced soil properties and increased plant growth. Its‘ recalcitrant characteristics are appropriate for tropical soils‘ organic matter management. Amending charcoal into BRIS soils could be a suitable measure in dealing with concerns regarding fertilizer losses due to excessive leaching process, which inadvertently leads to low yield production. A field study was conducted in Kg. Saujana, Setiu, Terengganu (05° 61393‘ N, 102° 73928‘ E) from April until July 2010 to assess kenaf response to the application of charcoal and fertilizer cultivated on BRIS (Rudua Series) soil. Five rates of NPK fertilizer (0, 0.2, 0.4, 0.6 and 0.8 t ha-1) and four rates of charcoal (0, 5, 10 and 15 t ha-1) with five replications were established with Factorial Randomized Complete Blocked Design (RCBD) on BRIS (Rudua Series) soil. The objectives of this study were to determine the chemical properties of charcoal, to determine effects of charcoal amendment on BRIS (Rudua series) soil as well as to determine the effect of charcoal and fertilization on kenaf growth and yield. Plants were maintained for 64 days and data on kenaf were categorized into yield (dry matter, biomass of aboveground plant and biomass of root) and growth components (heights, stem base diameter, leaf number, leaf length and leaf width). Soil sampling for determination of soil chemical properties were conducted on 30 and 64 days after planting (DAP). All data were analyzed using ANOVA of Minitab 17 for Windows and mean separation was conducted using Tukey test. In addition to field study, a leachate experiment was also conducted at the same study area to determine the effectiveness of charcoal application in reducing nutrient losses by controlling leaching process in the soil. Four rates of charcoal (0, 1, 2 and 3 kg pot-1) were mixed into pots containing 10 kg of BRIS (Rudua Series) soil each. Three hundred (300) g of fertilizer was applied into all pots excluding control. Leachate collection was based on rain intensity and analyzed for nitrogen (N) and potassium (K) content. All data were analyzed using ANOVA of Minitab 17 for Windows and mean separation was conducted using Tukey test. Results obtained revealed that rates of charcoal and fertilizer significantly affected (p ≤ 0.05) dry matter yield as well as fresh and dry biomass of kenaf. There were no significant differences (p ≥ 0.05) found in all growth components. Significant differences (p ≤ 0.05) were also found in nutrient content and nutrient use efficiency of kenaf plant tissue. Nitrogen (N), phosphorus (P) and potassium (K) content in plant tissue were significantly affected (p ≤ 0.05) by both single and interaction between charcoal and fertilizer factors. Significant effects (p ≤ 0.05) of single factor were observed in content of calcium (Ca) and magnesium (Mg). Both single and interaction between charcoal and fertilizer rates gave significant effects (p ≤ 0.05) on N, P and K use efficiency in this study. Significant effects (p ≤ 0.05) of interaction between charcoal and fertilizer rates were observed in soil total N, cation exchange capacity (CEC) and exchangeable Ca. Sampling times significantly affected (p ≤ 0.05) values of soil pHw, total N and available P. As for leachate experiment, there was no significant difference (p ≥ 0.05) in N and K content resulted from charcoal application. However, sampling times did significantly affected (p ≤ 0.05) the N content in collected leachate. Based on the results obtained from the study, it was concluded that charcoal had the potential as one of the sustainable amendments to BRIS (Rudua Series) soil in the respected area. The suitable combination rates of application for BRIS (Rudua Series) soil at the respected study site appeared to be at 10 t ha-1 charcoal and 0.6 t ha-1 fertilizer. Application of charcoal did significantly (p ≤ 0.05) enhanced the chemical properties of BRIS (Rudua Series) soil in the respected area. However, application of charcoal into soil should be conducted at least 2 months prior to planting for it to show positive effects on the soil. Results obtained from Study 2 revealed that application of charcoal into soil did not significantly (p ≥ 0.05) reduced the losses of N and K from the soil.